2018
DOI: 10.1021/acsmedchemlett.8b00498
|View full text |Cite
|
Sign up to set email alerts
|

Triazolopyrimidines and Imidazopyridines: Structure–Activity Relationships and in Vivo Efficacy for Trypanosomiasis

Abstract: Better therapeutics are greatly needed to treat patients infected with trypanosomatid parasites such as Trypanosoma cruzi or Trypanosoma brucei. This report describes 28 new imidazopyridines and triazolopyrimidines with potent and selective antitrypanosomal activity. Drug-like properties were demonstrated in a number of in vitro assays. In vivo efficacy was observed for 19 and 20 in acute mouse models of T. cruzi infection. Compounds 19 and 20 represent potential leads for new anti-Chagas disease drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Furthermore, these doses were lower than the curative dose of fexinidazole [9] (200 mg/kg) and comparable to that of acoziborole (25 mg/kg) [14]. A detailed structure activity relationship of TP class of compounds against both T. brucei and T. cruzi has been described by Nagendar and co-workers [23]. Although, one of their compounds, compound 20, had a brain-to-plasma ratio of 0.23, it was not profiled in the stage 2 HAT model, due to higher plasma protein binding (98.5%), which might affect free concentration in brain required for achieving stage 2 efficacy.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, these doses were lower than the curative dose of fexinidazole [9] (200 mg/kg) and comparable to that of acoziborole (25 mg/kg) [14]. A detailed structure activity relationship of TP class of compounds against both T. brucei and T. cruzi has been described by Nagendar and co-workers [23]. Although, one of their compounds, compound 20, had a brain-to-plasma ratio of 0.23, it was not profiled in the stage 2 HAT model, due to higher plasma protein binding (98.5%), which might affect free concentration in brain required for achieving stage 2 efficacy.…”
Section: Discussionmentioning
confidence: 71%
“…Based on the resistance of a T. brucei strain with a β4 mutation at F24 to HB175, it was concluded that this molecule is also a proteasome inhibitor ( Nagendar et al, 2018 ). A comparative study analyzed the effects of HB175 and 16 new imidazopyridines alongside GNF6702 and 12 new triazolopyrimidines, which showed that compounds of both classes kill T. brucei and intracellular T. cruzi at EC50s below 100 nM ( Nagendar et al, 2018 ). While the imidazopyridines were on average slightly more potent, they also showed greater toxicity against a human lymphocytic cell line.…”
Section: Inhibition Of the Proteasomementioning
confidence: 99%
“…One compound (11) had modest brain permeability of 9%, but was included for further chemistry despite this marginal activity. Four compounds (13)(14)(15)17) had minimal concentrations in the brain (< 2% of plasma levels) and were no longer pursued. One compound (16) had nearly undetectable plasma and brain levels at the 60-min time point and was also considered unsuitable for further development.…”
Section: Screening For Brain Permeabilitymentioning
confidence: 99%
“…Three scaffolds (1, 2, and 9) have been developed to the level of lead compounds ready for late preclinical studies [5,8,11,[14][15][16]. The optimization of hit compound 1 is shown in Figure 3 (Figure 3), the partially optimized compound (HB-175) is shown, which combines the best substituents of regions I, II, and III [5].…”
Section: Active Compound Series (Highlights)mentioning
confidence: 99%
See 1 more Smart Citation